Current trends in the management of Richter's syndrome. (8th January 2019) - Allan, John N; Furman, Richard R
Richter's syndrome (RS) is a life-threatening complication of chronic lymphocytic leukemia (CLL). While previous research has increased our knowledge on the distinct evolutionary patterns of RS and provided a deeper understanding of the risk factors and molecular events predisposing to transformation, there remain few targetable aberrations and treatment is largely ineffective. The ability to obtain deeper remissions, without selecting for deletion 17p, by using novel B-cell receptor (BCR) antagonists and bcl2 inhibition might lead to a decrease in the incidence of RS, but these agents have done little to significantly change outcomes when incorporated into treatment regimens for RS. In this review we highlight the current landscape of molecular lesions specific to RS, review the data on historical treatment options, and look to the horizon for potential opportunities in the future.